2020
DOI: 10.3390/ijms21031069
|View full text |Cite
|
Sign up to set email alerts
|

Current Biomedical Use of Copper Chelation Therapy

Abstract: Copper is an essential microelement that plays an important role in a wide variety of biological processes. Copper concentration has to be finely regulated, as any imbalance in its homeostasis can induce abnormalities. In particular, excess copper plays an important role in the etiopathogenesis of the genetic disease Wilson’s syndrome, in neurological and neurodegenerative pathologies such as Alzheimer’s and Parkinson’s diseases, in idiopathic pulmonary fibrosis, in diabetes, and in several forms of cancer. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
105
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 176 publications
0
105
0
1
Order By: Relevance
“…Chelation therapy has shown promise in the diseases including AD, PD, autism, cancer, cardiovascular disease, etc. [269,270]. Chelating agents not only reduces raised metal concentration but some thiol based chelators, such as meso 2,3-dimercaptosuccinic acid (DMSA), 2,3-dimercaptopropane 1-sulfonate (DMPS), D-pencillamine (DPA), and Monoisoamyldimercaptosuccinic acid (MiADMSA) ( Table 6) also have ROS neutralizing ability that can additionally diminish the augmented oxidative stress and further preventing cellular damage from oxidative insult [271].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Chelation therapy has shown promise in the diseases including AD, PD, autism, cancer, cardiovascular disease, etc. [269,270]. Chelating agents not only reduces raised metal concentration but some thiol based chelators, such as meso 2,3-dimercaptosuccinic acid (DMSA), 2,3-dimercaptopropane 1-sulfonate (DMPS), D-pencillamine (DPA), and Monoisoamyldimercaptosuccinic acid (MiADMSA) ( Table 6) also have ROS neutralizing ability that can additionally diminish the augmented oxidative stress and further preventing cellular damage from oxidative insult [271].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Different mechanisms are involved in copper drugs’ anticancer effect. They act as chelators, and interact with and sequester endogenous copper, reducing its availability for tumor growth and angiogenesis [ 39 ]. On the contrary, ionophores trigger intracellular copper accumulation, cytotoxicity, and activate apoptosis inhibitor factor (XIAP) [ 24 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased Cu concentration is associated with damages, including neurotoxicity [ 22 ] and neurological conditions such as Alzheimer's disease (AD), [ 23,24 ] Parkinson's disease, Menke's disease, Wilson's disease, and so forth. [ 1,11,25,26 ] For instance, studies revealed that Cu imbalance has widely affected the functions of neurons and may lead to cognitive deficits and AD pathology. [ 27 ] Also, it has been established that Cu accumulates in the amyloid β plaque of patients with AD.…”
Section: Introductionmentioning
confidence: 99%